(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article deals with the essence of financial security and the place of risk management in ensuring the necessary state of financial security of economic entities. The relationship between the concepts of risk and the threat to the financial security of business structures and the peculiarities of their interaction is shown. The essence of the system of financial risk-management is determined on the basis of system, institutional, process and functional approaches. Formulated principles, functions, objects, tasks of financial risk management as an instrument for achieving financial security of enterprises. The basic methods of risk assessment of business structures in the system of their financial security have been identified. Depending on the levels of implementation of financial risk management, strategic, tactical, operational risk management can be identified.